Intervention in nursing care for the elderly patients with alzheimer: integrative review - Luciana Póvoas Correa, Tayná Ramos Braga, Lucélia Cordeiro Malaquias, Maria Eliana Peixoto Bessa, Marília Braga Marques (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v5i1.3000